PENGAMAN SEPEDA MOTOR BERBASIS MIKROKONTROLER - Rino Reifano Rachmat; E. Shintadewi Julian (Website, 2016)
In this paper, we present an additional security device for motorcycles. When a motorcycle with this security device is stolen, the security device will stop the motorcycle from working and ring the alarm. The security system will also send an SMS and make 3 phone calls to the motorcycle owner’s mobile phone. The tests performed on a motorcycle brand